Household’s perception of water pollution and its economic impact on human health in Malaysia - Afroz, Rafia; Banna, Hasanul Banna; Mehedi Masud, Muhammad Mehedi; Akhtar, Rulia; Yahaya, Siti Rohani (Desalination Publications, 2016)
Environmental problems are a major global concern. In this global problem, water pollution is perhaps one of the more threatening causes of environmental problems. Water pollution significantly affects public health. Hence, this paper investigates household risk perception of water pollution and examines the demographic and socio-economic factors that influence their risk perception. The data was collected using a structured questionnaire and analysed by SPSS. The findings indicate that gender, age, education, income, AWN and ATT signifi- cantly affect household risk perception of water pollution. Upon discussing the water resource policies in Malaysia, we offer recommendations that will be helpful for policy- makers to improve river water quality in Malaysia.